The formation of the Victorian literary profession - Salmon, Richard, 1965- (Cambridge, UK ; New York : Cambridge University Press, 2013)
A fascinating study into the development of the Victorian literary profession that examines literary and visual representations of authorship.
Introduction: Living authors -- Thomas Carlyle and the luminous author -- Thackeray and the novel of literary apprenticeship -- Dickens and the profession of labour -- Broken idols: the development of the working-class author -- Moving statues: the iconography of the 'printing woman' -- Conclusion: The disenchantment of the author.
Includes bibliographical references (pages 259-273) and index.
Print version record.
eBooks on EBSCOhost
Keywords: English literature -- 19th century -- History and criticism; Authors in literature; Literature and society -- England -- History -- 19th century; Authors, English -- 19th century; England -- Intellectual life -- 19th century; Littérature anglaise -- 19e siècle -- Histoire et critique; Écrivains dans la littérature.; Littérature et société -- Angleterre -- Histoire -- 19e siècle.; Écrivains anglais -- 19e siècle.; Angleterre -- Vie intellectuelle -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Authors, English; Authors in literature; English literature; Intellectual life; Literature and society; England; 1800-1899; Criticism, interpretation, etc; History